2000
DOI: 10.1002/jor.1100180613
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprogenitor cells within skeletal muscle

Abstract: The formation of ectopic bone within skeletal muscle is a widely observed phenomenon. However, the source of the osteoprogenitor cells responsible for ectopic bone formation remains unknown. This study was designed to test for osteogenic differentiation among cells isolated from skeletal muscle tissue. Different subpopulations of cells derived from an adult mouse skeletal muscle were tested for induction of alkaline phosphatase activity after exposure to bone morphogenetic protein-2 in vitro. A responsive subp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
144
1
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 256 publications
(155 citation statements)
references
References 64 publications
7
144
1
3
Order By: Relevance
“…21 Indeed elevated levels of osteoblast stimulating factors have been identi®ed in SCI with heterotopic ossi®cation 30 and osteoprogenitor cells have been shown to reside within skeletal muscle. 31 Our ®ndings support the concept of HO as a complex, primarily in¯ammatory process possibly triggered by mechanical (microtraumatic) events. To de®ne the pathogenetic mechanisms responsible for HO, molecular studies (ie gene expression studies) of involved tissues appear necessary.…”
Section: Discussionsupporting
confidence: 80%
“…21 Indeed elevated levels of osteoblast stimulating factors have been identi®ed in SCI with heterotopic ossi®cation 30 and osteoprogenitor cells have been shown to reside within skeletal muscle. 31 Our ®ndings support the concept of HO as a complex, primarily in¯ammatory process possibly triggered by mechanical (microtraumatic) events. To de®ne the pathogenetic mechanisms responsible for HO, molecular studies (ie gene expression studies) of involved tissues appear necessary.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, recent studies have reported that these cells may exist in skeletal muscle. 7,9,[23][24][25][26][27][28][29] The presence of stem cells in skeletal muscle makes this tissue an attractive source of cells that are capable of enhancing the healing of various tissues. 9 In fact, we have recently observed that the genetic engineering of MDC (mc13) to express rhBMP-2 can be used to enhance closure of a non-healing skull defect.…”
Section: Discussionmentioning
confidence: 99%
“…23 It is now well established that muscle satellite cells are heterogenous and that skeletal muscle tissue may be a source for pluripotent stem cells. 7,9,[24][25][26][27][28][29] In particular, stem cell populations from muscle were recently shown to reconstitute the hematopoietic compartment of lethally irradiated mice and to partially restore the expression of dystrophin in the mdx mouse, an animal model of Duchenne muscular dystrophy. 7 In our laboratory, we have shown that the population of MDC (pp6) was, in fact, multipotent and had the capability of differentiating into other mesenchymal tissues, such as osteogenic lineage.…”
Section: Introductionmentioning
confidence: 99%
“…These cells fuse and align to form multinucleated primary myofibres. Previous studies have shown that skeletal muscle contains populations of osteoprogenitor cells, with ectopic bone formation being achieved experimentally using solubilised factors obtained from bone [46][47][48]. Evidence of an osteogenic capacity has also been recorded for both rat (L6 cells) and mouse (C2C12 cells) skeletal muscle myoblasts following transfection with osteogenic inducers, such as BMPs [49,50].…”
Section: Myoblastsmentioning
confidence: 99%